The effects of compassionate care on oral health outcomes: A scoping review - Mendes, Mariana Sarmet Smiderle [UNESP]; Ferreira, Camila Lopes; Jardini, Maria Aparecida Neves [UNESP]; Childs, Christopher Andrew; Marchini, Leonardo (Wiley, 2025)
Purpose: To access and synthesize the existing literature about the effects of compassionate care on oral health outcomes. Methods: A scoping review was performed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to identify articles from six electronic databases: MEDLINE via the PubMed interface, Embase, Age-Line, Scopus, CINAHL, and Cochrane. Results: Among 30 studies reporting on compassion in dental treatment, only two reported on the effects of compassionate care on oral health outcomes. One study is cross-sectional and evaluated oral health outcomes in children, while the other is a cohort study evaluating oral health outcomes in older adults. Each study used different tools to assess oral health outcomes. However, both studies used the Jefferson Scale of Physician Empathy (JSPE) to assess empathy among dental students, dentists, or dental hygienists. Conclusion: The retrieved studies used different methodologies and had discrepant results. More clinical studies investigating the effects of compassionate care on the outcomes of dental treatment are necessary.
Keywords: compassionate care; dental care; dentist-patient relations; empathy; oral health